The system of linear equations 3x + 2y + 8 = 0 and 7x + 8y = 9 has to be solved using substitution. 7x + 8y = 9 gives x = (9 - 8y)/7

Substitute this in 3x + 2y + 8 = 0

=> 3((9 - 8y)/7) + 2y = -8

=> 3*9/7 - 24y/7 + 2y = -8

=> 27/7 - 24y/7 + 2y = -8

=> 27/7 + 8 = 24/7y - 2y

=> (10/7)y = 83/7

=> y = 83/10

=> y = 8.3

x = (9 - 8y)/7

=> -8.2

**The solution of the set of equations is x = -8.2 and y = 8.3**

we have two equations

3x+2y+8=0

7x+8y=9

=> x=(-8y+9)/7

we substitute x in first equation

=> 3((-8y+9)/7)+2y=-8

(-24/7)y +(27/7)+2y=-8

(-10/7)y=-83/7

y=8.3

=> x=(-8(8.3)+9)/7=-8.2

=> the solution is :x=-8.2 and y=8.3

3x+2y+8-8=0-8

3x+2y=-8

3x+2y-3x=-8-3/x

2y=-8-3x

2y/2=-8/-3x/2

y=-4-3/2x

7x+8(-4-3/2x)=9

7x-32-12x=9

7x-32-12x+32=9+32

7x-12x=41

-5x=41

-5x/-5=41/-5

**x=-8.2**

y=-4-3/2(-8.2)

y=-4+12.3

**y=8.3**